Anterior cervical discectomy and self-sustaining cage placement in 10 steps - Álvarez Caicedo, Diana Carolina; Chuang, Joaquín; Pascual, Cintia; Sainz, Ariel; Erice, Santiago; Luque, Leopoldo Luciano (Revista Argentina de Neurocirugía, 2026)
Background: anterior cervical discectomy with cage placement is a commonly performed surgical technique, whose indication can range from simple hernias to complex deformity correction. Objectives: to describe the technique of anterior cervical discectomy and cage placement in 10 steps and to discuss its fundamental aspects. Description of technique: the 10 steps performed are described in detail: position, marking, approach, intraoperative check, placement of separators, discectomy, osteophyte drilling, posterior common vertebral ligament resection, cage placement and closure. Illustrations of the technique were attached for didactic purposes. Conclusion: anterior cervical discectomy with self-supporting cage placement is an efficient, reproducible, and safe surgical tool for the treatment of compressive cervical pathologies. Proper execution of the approach, considering both anatomy and surgical ergonomics, combined with correct indication of the type of implant and selective opening of the posterior common vertebral ligament resection, allows for optimization of clinical results and minimization of complications. The 10-step systematic technique presented in this paper can serve as a simple and detailed guide to follow, reducing the margin of error and providing better surgical results.